Combining biological and socio-political criteria to set spatial conservation priorities for the endangered African wild dog - Kuiper, T; Dickman, A; Hinks, A; Sillero-Zubiri, C; Macdonald, E; Macdonald, D (Wiley, 2018)
Conservation effectiveness is influenced by socio-political context, a reality overlooked by traditional prioritisation schemes that use only measures of biological value and threat when deciding where to invest limited conservation resources. We combined ecological and socio-political criteria to illuminate options for prioritising investment in African wild dog Lycaon pictus conservation among countries and subpopulations. Countries were assigned scores for conservation priority (based on their wild dog populations) and conservation likelihood (based on their governance quality and other indicators of the likelihood of effective conservation action for wild dogs). Seven of the 19 wild dog countries scored above the median value for both priority and likelihood and supported 70% of the total wild dog population. Investment in these ‘higher priority, higher-likelihood’ countries may offer the greatest returns on conservation investment. The intention of this study is not, however, to be prescriptive, nor to suggest abandoning disadvantaged countries, but to provide a tool for understanding and managing trade-offs between where conservation is most needed for wild dogs and where it is most feasible. The prioritisation framework presented in this paper may easily and profitably be applied to other taxa, extending the scope of our results.